A somatic splice‐site variant in PIK3R1 in a patient with vascular overgrowth and low immunoglobulin levels: A case report - Matheus V. M. B. Wilke; Lisa Schimmenti; Madeline Q. R. Lopour; Megha M. Tollefson; Eric W. Klee (Molecular Genetics & Genomic Medicine, 2023)
Abstract Background The PI3K/AKT pathway, extensively studied in cancer, is vital for regulating cell metabolism, differentiation, and proliferation. Pathogenic variants in the PIK3R1 gene, which encodes three regulatory units of class IA PI3Ks, have been found in affected tissue of individuals with vascular lesions. These variants predominantly occur in the iSH2 domain, disrupting inhibitory contacts with the catalytic unit and leading to PI3K activation. Germline variants in this gene are also linked to an immunological condition called Activated PI3K delta syndrome type 2 (APDS2). Methods This is a case report and literature review. Clinical data were retrieved from medical records. Results A male patient presented with extensive vascular malformation covering over 90% of his body, along with complete 2–3 toe syndactyly, suggesting a vascular malformation syndrome called PROS. Low levels of IgA and IgG were detected. The patient achieved his developmental milestones and had above‐average weight, height, and head circumference. Exome sequencing of skin and blood DNA revealed a de novo variant in PIK3R1 (c.1746‐2A>G, p.?) in 9% of the patient's blood cells and 25% of cultured fibroblasts. Initially, classified as a variant of uncertain significance, this variant was later confirmed to be the cause. Conclusions This is the first intronic SNV in a canonical splice site within iSH2 described, highlighting the importance of iSH2 in the regulation of the PI3K/AKT pathway and its involvement in the development of vascular overgrowth and antibody deficiency.